Deficiency of aminopeptidase P1 causes behavioral hyperactivity, cognitive deficits, and hippocampal neurodegeneration. (15th September 2017) - Bae, Y.‐S.; Yoon, S. H.; Han, J. Y.; Woo, J.; Cho, Y. S.; Kwon, S.‐K.; Bae, Y. C.; Kim, D.; Kim, E.; Kim, M.‐H.
Abstract : Metabolic diseases affect various organs including the brain. Accumulation or depletion of substrates frequently leads to brain injury and dysfunction. Deficiency of aminopeptidase P1, a cytosolic proline‐specific peptidase encoded by the Xpnpep1 gene, causes an inborn error of metabolism (IEM) characterized by peptiduria in humans. We previously reported that knockout of aminopeptidase P1 in mice causes neurodevelopmental disorders and peptiduria. However, little is known about the pathophysiological role of aminopeptidase P1 in the brain. Here, we show that loss of aminopeptidase P1 causes behavioral and neurological deficits in mice. Mice deficient in aminopeptidase P1 (Xpnpep1 −/− ) display abnormally enhanced locomotor activities in both the home cage and open‐field box. The aminopeptidase P1 deficiency in mice also resulted in severe impairments in novel‐object recognition, the Morris water maze task, and contextual, but not cued, fear memory. These behavioral dysfunctions were accompanied by epileptiform electroencephalogram activity and neurodegeneration in the hippocampus. However, mice with a heterozygous mutation for aminopeptidase P1 (Xpnpep1 +/− ) exhibited normal behaviors and brain structure. These results suggest that loss of aminopeptidase P1 leads to behavioral, cognitive and neurological deficits. This study may provide insight into new pathogenic mechanisms for brain dysfunction related to IEMs. Abstract : The metabolic dysfunction caused by the loss of aminopeptidase P1 causes severe behavioral and neurological deficits in mice.